Industrial policy: a tale of innovators, champions, and B52s - Armin Riess; Timo Välilä (EIB Papers, 2006)
Recognising and discussing the elusiveness of industrial policy as a distinct policy concept, this paper argues against what probably is the most extreme type of so-called 'vertical' industrial policy, that is, support for national or European champions. It also critically reviews the rationale for one of the economically most appealing so-called 'horizontal' industrial policies, that is, support for research and development. Although not disputing that there is a rationale for such support, we reason that it is not as strong as commonly assumed. In this context, we find that while competition is key for spurring innovation and growth, there is room for industrial policy - interestingly enough, not so much to encourage firms to extend the technological frontier, but to catch up with it. The paper also previews the other contributions to this volume of the EIB Papers.
Keywords: 330; Industriepolitik; EU-Staaten